THE ROLE OF PARENTS IN REDUCING GADGET DEPENDENCE AMONG PRESCHOOL-AGED CHILDREN THROUGH THE INSTILLATION OF ISLAMIC EDUCATIONAL VALUES AT KARTIKA PRESCHOOL - Vicha Alfinejm.A; Asmawati; Anisah; Husin (Academic Bright Collaboration, 2026)
This study aims to analyze the role of parents in reducing gadget dependence among early childhood students through the instillation of Islamic educational values at Kartika Kindergarten, Rawa Jaya Village, South Tabir Subdistrict, Merangin Regency. Specifically, this study examines how parenting practices based on Islamic values are applied in a local context to limit gadget use among early childhood students. This study employs a qualitative approach using field research. Data were collected through observation, interviews, and documentation from informants consisting of the principal, teachers, parents, and children at Kartika Kindergarten. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, while data validity was tested using source triangulation and methodological triangulation. The results of the study indicate that parents fulfill the roles of educators, mentors, supervisors, and role models in regulating their children’s gadget use. The most notable finding indicates that restrictions on gadget use are more effective when combined with fostering religious practices, setting a good example, intensive communication between parents and children, and redirecting children’s time toward religious activities, play, and learning that involve collaboration between families and the school. These practices constitute the primary characteristics of the implementation of Islamic educational values at Kartika Kindergarten. The research findings suggest that instilling Islamic educational values through active parental involvement can be a relevant strategy in supporting the regulation of gadget use among young children. However, this study did not quantitatively test the effectiveness of these strategies. Additionally, the research was conducted at only one educational institution, so the results cannot yet be generalized to a broader context. This study contributes by demonstrating how the integration of parental roles and Islamic educational values is applied contextually in early childhood education in a rural setting. The study shows that collaboration between families and schools is a key factor in fostering more purposeful gadget-use habits while simultaneously strengthening the development of children’s religious character.